Kecebong Versus Kampret; Slogan Negatif Dalam Komunikasi Politik Pada Pemilihan Presiden 2019 - Nur Rohim Yunus; Ida Susilowati; Zahrotunnimah Zahrotunnimah (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2019)
As the largest democratic party in any region, presidential elections are often followed by campaigns as a means of political socialization in general elections. Likewise what happened in the 2019 presidential election in Indonesia. Unfortunately, the campaign found some negative propaganda through the slogans of each of the supporters of the two candidate pairs. Ironically, this slogan seems to divide the Indonesian people into two big camps with the name of an animal that is not suitable for humans. The term